Chidamide and anlotinib synergistically inhibit high grade B-cell lymphomas via PI3K/AKT signaling pathway - Jiazhen Lin; Xinguo Zhuang; Shuman Jia; Hui Zhou; Dongmei Qin; Jie Zhou; Yiming Luo; Bing Xu; Jie Zha (Scientific Reports)
Abstract High-grade B-cell lymphoma with concurrent MYC and BCL2/BCL6 rearrangements (HGBL-DHL) is a challenging disease resistant to front-line immunochemotherapies, which urgently requires novel therapeutic approaches. Herein, combination of chidamide and anlotinib demonstrated potential synergistic anti-lymphoma effects against HGBL-DHL. The cooperative effect of cell proliferation inhibition, apoptosis induction, and cell cycle arrest were demonstrated in cell lines through Cell Counting Kit-8, Annexin V/PI staining, and PI staining respectively. Moreover, in an HGBL-DHL-xenografted mouse model, the combination therapy markedly reduced tumor burden without inducing fatal toxicity. Mechanistically, chidamide suppressed HDAC3, while anlotinib inhibited VEGFR2, both leading to down-regulation of the PI3K/AKT signaling cascade. This dual suppression occurred as a result of their synergistic interaction. Downstream targets of the PI3K/AKT signaling pathway including proliferation-associated protein c-Myc, anti-apoptotic proteins BCL2 and MCL1, and cell cycle-associated protein cyclin A2 were all synergistically down-regulated, which coincided with the phenotypic outcomes. Collectively, our preclinical findings underscored the synergistic activity of chidamide and anlotinib combination against HGBL-DHL, warranting further clinical evaluation of this regimen for treating this challenging entity.